2015
DOI: 10.1002/mds.26413
|View full text |Cite
|
Sign up to set email alerts
|

REM sleep behavior disorder, as assessed by questionnaire, in G2019S LRRK2 mutation PD and carriers

Abstract: Background Rapid eye movement sleep Behavior Disorder occurs with idiopathic Parkinson disease (PD), and often precedes PD. Its frequency in LRRK2-PD and utility as a pre-clinical marker has not been established. Methods 144 idiopathic PD, 142 LRRK2 G2019S mutation PD, 117 non-manifesting carriers, 93 related non-carriers, and 40 controls completed the Rapid eye movement sleep Behavior Disorder Screening Questionnaire. Results 30.6% idiopathic PD, 19.7% LRRK2-PD, 6% non-manifesting carriers, 20.4% related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 41 publications
4
18
1
Order By: Relevance
“…In accord with earlier reports, HC demonstrated slightly more nonmotor symptoms, such as constipation and depression, compared to HNC. Previous studies reported less hyposmia and RBD in patients with AJ and non AJ LRRK2 ‐PD, as compared to idiopathic PD cases ,. Consistent with these findings, olfaction did not differ between HC and HNC whereas there was a trend for less RBD in HC than HNC.…”
Section: Discussionsupporting
confidence: 84%
“…In accord with earlier reports, HC demonstrated slightly more nonmotor symptoms, such as constipation and depression, compared to HNC. Previous studies reported less hyposmia and RBD in patients with AJ and non AJ LRRK2 ‐PD, as compared to idiopathic PD cases ,. Consistent with these findings, olfaction did not differ between HC and HNC whereas there was a trend for less RBD in HC than HNC.…”
Section: Discussionsupporting
confidence: 84%
“…and although DLB was reported to be associated with the APOE 4 allele (Kobayashi, et al, 2011,Lane, et al, 2009), our results demonstrate lack of association between the APOE 4 allele and RBD or its age at onset. These and previous results ,Saunders-Pullman, et al, 2015 further suggest that RBD may have a distinct genetic background; it is associated with GBA mutations , but unlike PD it is not associated with LRRK2 mutations ,Saunders-Pullman, et al, 2015, and unlike DLB it is not associated with the APOE 4 allele. Thus far, GBA, SCARB2, and potentially SNCA overlap between RBD, PD and DLB (Figure 1) (Bras, et al, 2014.…”
Section: Discussionsupporting
confidence: 63%
“…Conversely, mutations in LRRK2 were not associated with RBD ,Pont-Sunyer, et al, 2015,Saunders-Pullman, et al, 2015, further supporting the hypothesis that RBD has a distinct genetic background.…”
Section: Introductionsupporting
confidence: 59%
“…It may be relevant that the prior reports did not perform adjusted analyses. Three groups using samples overlapping with ours have reported lower RBDSQ scores in LRRK2 G2019S PD than in iPD 15,32,33 Although not reaching statistical significance, a lower proportion of LRRK2 G2019S PD participants in our sample reported symptoms suggestive of RBD. In iPD, RBD has proven to be the strongest known risk factor for the development of PD.…”
Section: Discussioncontrasting
confidence: 61%